2014
DOI: 10.1097/ccm.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Medical Emergency Team Using an Electronic Medical Recording–Based Screening System*

Abstract: We successful managed the medical emergency team with electronic medical record-based screening criteria and a skilled intervention team. The electronic medical record-triggered group had lower ICU admission than the call-triggered group or the double-triggered group. In surgical patients, the electronic medical record-triggered group showed better outcome than other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Huh and colleagues demonstrated a reduction in ICU transfers using a single parameter activation criteria system (18). And Bellomo et al demonstrated a reduction in mortality in a multicenter heterogeneous intervention (19).…”
Section: Discussionmentioning
confidence: 99%
“…Huh and colleagues demonstrated a reduction in ICU transfers using a single parameter activation criteria system (18). And Bellomo et al demonstrated a reduction in mortality in a multicenter heterogeneous intervention (19).…”
Section: Discussionmentioning
confidence: 99%
“…One of the unique aspects of some EHRs is the ability to capture dense longitudinal information on patients. These data may consist of, for example, respiratory measurements from an intensive care unit 1 or heart rate measurements from a surgical procedure 2 . Such data present the opportunity to observe and analyze a patient’s changing vital signs over time.…”
Section: Introductionmentioning
confidence: 99%
“…There is some debate whether plasma cTn is an independent prognostic marker in sepsis or simply a surrogate for overall severity of illness (4,6). cTn abnormalities are also common in the postoperative setting (14), but some clinicians have argued that routine testing may simply increase the risk of harm from inappropriate treatment for myocardial infarction (15). However, the work by Landesberg et al suggests that there may be value in investigating the cause of cTn abnormalities in sepsis using echocardiography to identify and assess potential targets for therapy.…”
mentioning
confidence: 97%
“…In this issue of Critical Care Medicine, Huh et al (14) attempted to overcome afferent limb RRS failure through modifying human computer interaction, using EHR as a screening tool linked to automated RRT activation. After predefined criteria were met, automatic activation of RRT through EHR screening (named electronic medical record…”
mentioning
confidence: 99%